Multiscale magnetization in cobalt‐doped ferrite nanocubes. Issue 6 (1st December 2022) - Zákutná, Dominika; Fischer, Anne; Dresen, Dominique; Nižňanský, Daniel; Honecker, Dirk; Disch, Sabrina
Abstract : This article presents a set of cuboidal cobalt ferrite nanoparticles with exceptionally high crystallinity, revealed by homogeneous magnetization with negligible near‐surface spin disorder as observed by magnetic small‐angle neutron scattering. Abstract : The magnetization of cobalt ferrite nanocubes of similar size, but with varying Co/Fe ratio, is extensively characterized on atomistic and nanoscopic length scales. Combination of X‐ray diffraction, Mössbauer spectroscopy, magnetization measurements and polarized small‐angle neutron scattering (SANS) reveals that a lower amount of cobalt leads to an enhanced magnetization. At the same time, magnetic SANS confirms no or negligible near‐surface spin disorder in these highly crystalline, homogeneously magnetized nanoparticles, resulting in an exceptionally hard magnetic material with high coercivity.